An outline of future-oriented dialectics: Conceptualising dialectical positions, trajectories and processes in the context of futures research. (October 2022) - Ahlqvist, Toni
Abstract: The paper outlines a dialectical approach to analyse societal tendencies by emphasising future tensions, contradictions and antagonisms. First, the theoretical baseline of the approach is a commitment to the basic tenet of dialectical thinking: a perspective of the world as a process and a becoming. Second, the approach focuses on societal and socio-technical change trajectories and various dynamics in between. Third, it is based on systems and complexity thinking, particularly the idea of a societal system consisting of various parallel and contradictory trajectories. Methodologically, the approach emphasises dialectical thinking in two lenses: positions and processes. Dialectical positionality refers to basic dialectical positions as outcomes of the dynamics between the spatiotemporal trajectories in the societal system. Dialectical processuality refers to the processual nature of future-oriented dialectics, that is, the unravelling of the spatio-temporal processes and trajectories that lead to changes in the societal system. Dialectical processes are divided into two dynamic levels: trajectory and system. The paper presents stylised examples of positions and processes on these two levels. Highlights: The paper provides arguments for why dialectical thinking is important theoretical avenue for contemplating future technological transformations in liberal societies. The paper conceptualises a future-oriented dialectics for the analysis of dialectical positions and dialectical processes in the context societal and socio-technical trajectories. The dialectical positions emphasise arrangements that condition societal trajectories, such as tensions, contradiction and antagonisms. The dialectical processes highlight societal development tendencies at the levels of trajectories and systems. The paper provides stylised examples of the dialectical positions and processes.